SH2 domains of the p85 alpha subunit of phosphatidylinositol 3-kinase regulate binding to growth factor receptors. - McGlade, C J (1992)
The binding of cytoplasmic signaling proteins such as phospholipase C-gamma 1 and Ras GTPase-activating protein to autophosphorylated growth factor receptors is directed by their noncatalytic Src homology region 2 (SH2) domains. The p85 alpha regulatory subunit of phosphatidylinositol (PI) 3-kinase, which associates with several receptor protein-tyrosine kinases, also contains two SH2 domains. Both p85 alpha SH2 domains, when expressed individually as fusion proteins in bacteria, bound stably to the activated beta receptor for platelet-derived growth factor (PDGF). Complex formation required PDGF stimulation and was dependent on receptor tyrosine kinase activity. The bacterial p85 alpha SH2 domains recognized activated beta PDGF receptor which had been immobilized on a filter, indicating that SH2 domains contact autophosphorylated receptors directly. Several receptor tyrosine kinases within the PDGF receptor subfamily, including the colony-stimulating factor 1 receptor and the Steel factor receptor (Kit), also associate with PI 3-kinase in vivo. Bacterially expressed SH2 domains derived from the p85 alpha subunit of PI 3-kinase bound in vitro to the activated colony-stimulating factor 1 receptor and to Kit. We infer that the SH2 domains of p85 alpha bind to high-affinity sites on these receptors, whose creation is dependent on receptor autophosphorylation. The SH2 domains of p85 are therefore primarily responsible for the binding of PI 3-kinase to activated growth factor receptors.